THE EXPRESSION OF ARCHITECT MILOSAV MIŠA MITIĆ (1932–1970) IN THE 1960s: THE SEARCH, CRYSTALLIZATION AND MATURITY - Anđelković, Goran V. (Arhitektura i urbanizam, 2021)
The subject of the research is the beginning of the design work and professional engagement of architect Milosav Miša Mitić in the 1960s. Until now, this period of Mitić’s design practice and construction activity has not been the subject of any scientific research, and it has still not been assessed in architectural historiography. The aims of the paper are to shed light on the lesser-known facts about Mitić’s work at the beginning of his professional career, to determine the basic characteristics of his practice and to critically re-examine his contribution to the overall picture of Serbian architecture in the second half of the twentieth century. The scientific analysis covers significant unrealized and accomplished architectural achievements, both independently in the project studio Atrium (1956–1959), and jointly within the architectural group Belgrade Five (1954–1970). It examines in detail Mitić’s developmental creative path in three phases (1956–1960): the search for authorial expression during the 1950s in the project studio Atrium, when his authorial duality comes to the fore, imbued with a strong sense of modus operandi and modus vivendi; crystallization of the author’s expression within a five-member group, through a series of competitions and the first major accomplished project in the first housing estate within the Central zone of New Belgrade; and reaching full authorial maturity in his first major independent contracted design and construction project, for the EFGH local community center complex, with the S-10 commercial and residential tower. This is historical evidence of the possible different physiognomy of the future center of New Belgrade, with its recognizable architecture.